Mercenaries or refugees? the evidence from the inscriptions of Merenptah on the ‘Sea Peoples’ - Kopanias, Konstantinos (Journal of Greek Archaeology, 2017)
During the fifth regnal year of Merenptah (either 1208 BC or 1219 BC), king Merey of the Rebu/Lebu attacked Egypt, together with his archers and many northern warriors. These northerners were not affiliated with any of the existing minor or major kingdoms of the eastern Mediterranean, since they are only identified by obscure ethnonyms. Five inscriptions of Merenptah refer to these particular events, but they offer scarce historical information; a sixth one, inscribed on a wall of the Amun temple in Karnak, is the most elaborate one. Although the Karnak inscription has often been cited, most scholars usually focus on the parts referring to the ‘Sea Peoples’, which are often examined in isolation and out of their context. The aim of this paper is to re-examine the available evidence.